Pembuatan Tabel Microsoft Excel Dan Rumus Fungsi Microsoft Excel Untuk Data Kesehatan - Maureen Tumalun; Melky Pangemanan; Augustinus Robin Butarbutar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Microsoft Excel is a versatile tool for data analysis that can be used in various contexts, including health. This study focuses on the use of Excel to manage and analyze health data. The process begins with the creation of Excel tables that include health data such as weight, height, blood pressure, and blood sugar levels. Next, we apply various Excel formulas and functions to interpret this data. Examples include the use of the SUM function to sum data, the AVERAGE function to calculate averages, and the IF function to create conditional statements to determine a person's health status based on certain parameters. The results show that Microsoft Excel is a powerful and effective tool for managing health data and provides valuable insights for health analysis. This research provides a strong foundation for the use of Excel in the health context and highlights the importance of a thorough understanding of Excel formulas and functions for accurate and informative data analysis.